Aqueous alteration of Yamato 000749 based on multi-probe microscopic observation - Shiraishi, Naoki; Suga, Hiroki; Miyahara, Masaaki; Ohigashi, Takuji; Inagaki, Yuichi; Yamaguchi, Akira; Tomioka, Naotaka; Kodama, Yu; Ohtani, Eiji (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites / Hayabusa, Tue. 4 Dec. / Conference hall of the Research/Administration Building (2nd floor) at the JAXA Sagamihara Campus conference object